From the epicardial adipose tissue to vulnerable coronary plaques - Echavarría-Pinto, Mauro (Baishideng Publishing Group Co., Limited, 2013)
Thin cap fibroatheromas (TCFAs) are thought to be the most common underlying substrate in patients suffering acute coronary thrombotic events. Recently, an interesting association between TCFAs and a particular depot of visceral fat called epicardial adipose tissue (EAT) has been suggested. In this article, we discuss some basic and clinical aspects of this association and then briefly review some of the pathophysiological characteristics attributed to EAT that explain why this particular depot of fat has been attracting the attention of the cardiological scientific community in recent years. Finally we discuss the value of optical coherence tomography in the diagnosis of TCFAs and the role of multislice computed tomography to assess EAT.